Motor skills and morphological characteristics of handball players at different levels of competition - Vojinovic, A. (2nd International scientific conference "Sport, recreation, health", 12th & 13th May, 2017, Belgrade, 2017)
The survey was conducted on a sample of 24 patients who were divided into two groups according to the ranks of the competition. The study used experimental methods transversal type. The results were analyzed by descriptive statistics and comparative statistics where it is applied a single analysis of variance (ANOVA). The level of statistical significance was p <0.05. Results indicate that there are statistically significant differences in body weight between the participants at the level of significance p = 0.009 *, percentage of muscle tissue at the level of significance p = 0.006 * statistically significant difference of body mass index to the level of significance p = 0.019 * in favor of the higher-ranking players. Based on the analysis of the results showed that there were no statistically significant differences in body height and body fat surveyed groups. The motor variables there were some surprises. It had been expected that higher-ranking handball competition to achieve better results, but they are only the variables agility and coordination achieved better results. In other variables jumping ability, speed and flexibility had similar results. Keywords: handball, morphology, motor skills, testing